REASSESSING THE ROLES OF THE YANG DI-PERTUAN AGONG AND THE RULERS IN THE MAKING OF INTERNATIONAL TREATIES (UUM Journal of Legal Studies, 2020)
Malaysia continuously negotiates, signs and ratifies international treaties to foster closer relationship with its counterparts. The Federal Constitution of Malaysia provides no direct provision in granting treaty-making capacity to a specific person(s) or institution(s). However, it may be deduced from the available provisions that such power is exercisbale by the executive arm of the Federal Government. By definition, the executive includes the Yang di-Pertuan Agong, which is elected among the Malay Rulers by the Conference of Rulers. This paper reassesses the roles and functions of the Yang di-Pertuan Agong and the Rulers in the making of international treaties. The study is carried out using library based research method that assesses the provisions of the Federal Constitution, local case(s) and international conventions, in particular the Vienna Convention on the Law of Treaties 1969. The paper will delve into the available legal documents to explain the functions of the Yang di-Pertuan Agong and the Rulers under the Federal Constitution and accordingly reassess the legal position of the the Yang di-Pertuan Agong and the Rulers in the making of international treaties. The finding of this paper will show that, in practice, the Yang di-Pertuan Agong and the Rulers hve no the executive power to conclude and sign international treaties. Nonetheless, the Federal Constitution does confer certain limited powers on the Yang di-Pertuan Agong and the Rulers that may indirectly influence the making of international treaties. These roles are normally consultative in nature.